Regions of war and peace - Lemke, Douglas, 1967- (Cambridge studies in international relations, 2002)
Douglas Lemke's book asks whether the causes of war among great powers also apply to other countries, given different regional circumstances and historical experiences. The book examines Africa, the Far East, the Middle East and South America, and argues that the causes of wars are similar across these regions.